UPACARA TINJU ADAT ETU PADA MASYARAKAT DESA LEGUDERU KECAMATAN BOAWAE KABUPATEN NAGEKEO NUSA TENGGARA TIMUR - Prastiwi, Olala Osprey Munggur (HOLISTIK, Journal of Social and Culture, 2024)
Flores Island is one of the islands of a series of island groups which are part of East Nusa Tenggara Province. The people of Flores are actually not one tribe with one culture that is entirely uniform. Nagekeo Regency has a lot of potential wealth ranging from the uniqueness of natural resources to a variety of cultures that are different from other districts in East Nusa Tenggara. The number of tribes and customs in Indonesia is one of the factors in the development of culture. Culture is inherited from generation to generation from ancestors which is manifested in customs, traditions, and ceremonies as important elements. One of the traditional ceremonies in Nagekeo culture that aims as a form of community gratitude to commemorate the harvest day of the fields is the Traditional Boxing Ceremony, in the regional language called Etu. The Etu Traditional Boxing Ceremony is a cultural performance as one of a series of traditional events. In its implementation, the ceremony involves many communities with their respective roles. Such as community groups that play a role in preparing the ceremony, community groups that play a role during the implementation of the ceremony, and community groups that play a role in the stages after the ceremony takes place. The momentum of the Etu Traditional Boxing Ceremony can bring together people from various tribes and regions who come to watch the ceremony. This is where there will be communication between various tribes that can unite the community, especially in Nagekeo Regency. Keywords: ceremony, sport, Etu traditional boxing